4-Cs: TEACHERS' EFFORTS TO TRANSFORM 21ST CENTURY SKILLS IN TEACHING AND LEARNING - Sukirwan, Sukirwan; Ratnaningsih, Nani; Patmawati, Hetty; Suhaya, Suhaya (Journal of Authentic Research on Mathematics Education (JARME), 2024)
This research targets teachers' efforts to transform 21st-century skills in learning. A total of 30 lesson plans made by elementary school teachers participating in the Sultan Ageng Tirtayasa University Teacher Professional Education training in 2021-2022 were analyzed based on the accuracy of using operational verbs used by teachers in describing 4-Cs (critical thinking and problem solving, creativity and innovation, communication, and collaboration), compared to verbs/base outcomes on the Central Board of Secondary Education (CBSE). This research uses the content analysis method, with stages: formulating problems, selecting samples/sources of research data, categorizing, coding, clarifying summary content, analyzing coding results, and presenting and interpreting data based on theories or hypotheses of thought. Data analysis uses qualitative analysis, including data reduction, presentation, conclusion drawing, and verification. The results of the research obtained are (1) in transforming 21st-century skills, the level of teacher understanding of communication skills is the best compared to other 4-Cs, (2) teachers have low pedagogic and professional knowledge, this is shown by the mistakes made by teachers in choosing the correct operational verbs to describe 4-Cs in designing learning. This study also recommends upgrading and increasing teachers' understanding of the 4 Cs in realizing 21st-century learning by curriculum and policy achievements that are right on target.